ANALISIS KADAR TANIN BERBAGAI JENIS TEH HITAM DAN TEH HIJAU KHAS KOTA PAGARALAM SEBAGAI ANTIOKSIDAN MENGGUNAKAN METODE SPEKTROFOTOMETER UV-VIS - Krishna, lora Krisina (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
The plant known as tea (Camellia sinensis L.) is widely grown in Indonesia. The shoots of young tea leaves are brewed into a health drink. This research was carried out with the aim of determining the tannin content of green tea and black tea as well as their antioxidant activity using the UV-Vis spectrophotometer method. Thick extracts from black tea and green tea from qualitative and quantitative test results showed the presence of tannin compounds with tannin levels in the samples obtained were T1 Black tea (CTC Tea) Slopes of Mount Dempo 0.070, T2 Green tea (PTPN 7) Pagaralam tea typical of South Sumatra 0.061, T3 Green tea (PTPN 7) Gunung Dempo 0.028, T4 Black Tea (CTC Tea) Pucuk Gunung Dempo 0.059, and antioxidant activity was tested using 2,2 diphenyl-1-picrylhydrazyl (DPPH). Black tea and green tea extracts have antioxidant activity with a value of IC50 (Inhibition Concentration 50). T1 has very strong antioxidant activity (13.89%), followed by code T2, the antioxidant activity is also very strong (3.67%), code T3 has very strong antioxidant activity. strong (2.02 %), and T4 code moderate antioxidant activity (6.02 %). Black tea and green tea extracts contain high levels of tannin and have very strong antioxidant activity.